Cosmovisões: (in)visibilidades das marcas discursivas voltadas à formação humana em projetos político-pedagógicos de instituições de ensino - Domingues, Gleyds Silva (2015)
A worldview is seated within a system of beliefs which is present in social reality in the way men and women weave readings about life. This indicates that the worldviews talk about the subjects and in this discourse one can perceive the multiplicity of voices which find each other, confront themselves, complement themselves and unsay things the meanings attributed to life. With this in view, it is necessary to investigate how these meanings gain life in the school context, based on what is proposed in the political-pedagogical projects, with the goal of verifying the presence of the worldviews in the practices carried out, understanding the presence of the (in) visibility of the constructed discursive marks in the context of five schools, public and private, based on the line of action: lay and confessional which become a defender of a human education proposal. The problem to be analyzed has as its guiding and central issue the following reflection: How is it possible to identify the worldviews which are underlying the political-pedagogical projects based on the foundations which delineate the proposals defended of human education? For this proposal discursive construction theoretical referentials were chosen which are situated in the context of the issues raised so as to point out arguments and foundational concepts present in the investigated worldviews; identify the interpretational lenses of the chosen worldviews in the attempt to point out the (in) visibility of the educational process in the construction of the discursive marks aimed at human education; analyze the political-pedagogical projects based on the discursive analysis of human formation and the way in which they explain the system of beliefs in the act of teaching and of learning; and delineate possibilities of approximations between the worldviews as they provoke confrontation and point to existing gaps in the act of human education, evidenced within the lived out and prescribed curriculum. The theoretical-methodological axis of the research is the discourse analysis which has as its goal to understand how the meanings are constructed in social reality. One must point out that the meanings given to the education actions do not always correspond to the discourses defended in the documents of the school, which indicates the presence of a polissemy of meaning which can be manifest by the positions assumed by the men and women who carry within themselves their own worldview.